2015
DOI: 10.1590/1807-1929/agriambi.v19n8p773-779
|View full text |Cite
|
Sign up to set email alerts
|

Yield of castor bean fertilized with sewage sludge and potassium and magnesium sulphate

Abstract: <title>ABSTRACT</title><p>The aim of this study was to evaluate the yield and nutrition of castor bean in response to fertilization with sewage sludge and potassium (K) and magnesium (Mg) sulphate. The experiment was carried out from January to July 2011. The treatments, in a randomized block design with three replicates, in a Nitosol, corresponded to a factorial scheme (2 x 4 +1): two doses of K and Mg sulphate combined with four doses of sewage sludge (0, 2.60, 5.20 and 10.40 t ha<sup>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Some studies have reported that the addition of sewage sludge to the soil increases the productivity of the castor bean crop, resulting in high dry matter and seed oil yield (Capuani et al, 2015;Maciel-Torres et al, 2017). Cavalcanti et al (2015) reported that the productivity of castor bean fertilized with sewage sludge and potassium magnesium sulphate was similar to that found with NPK fertilization, indicating the potential of this residue as a substitute for mineral fertilization.…”
Section: Discussionmentioning
confidence: 93%
“…Some studies have reported that the addition of sewage sludge to the soil increases the productivity of the castor bean crop, resulting in high dry matter and seed oil yield (Capuani et al, 2015;Maciel-Torres et al, 2017). Cavalcanti et al (2015) reported that the productivity of castor bean fertilized with sewage sludge and potassium magnesium sulphate was similar to that found with NPK fertilization, indicating the potential of this residue as a substitute for mineral fertilization.…”
Section: Discussionmentioning
confidence: 93%
“…The zinc contents (Zn 2+ ) showed an increase with high correlation on the SS fertilizations at the 0 to10 cm depth (p<0.05) (Table 3 and Figure 1). The increments on the Zn 2+ contents on the soil with the use of SS have been observed on several researches on tropical soils (Zuba Junio et al, 2012;Nascimento et al, 2014;Cavalcanti et al, 2015) and, depending on the chemical characteristic of this organic fertilizer, the supply of the micronutrient may reach levels higher than 4 kg ha -1 (Albuquerque et al, 2015).…”
Section: Cation Micronutrients and Heavy Metals In The Soilmentioning
confidence: 89%
“…The productivity results obtained are considered close to the Brazilian means on single production systems with soy beans on the 2014-2015 crop, estimated at 3.016 kg ha -1 , according to the National Supply Company (Conab, 2015). The use of SS has also shown an increase on the productivity of sunflower seeds (Albuquerque et al, (2015), in addition to similar productivities when mineral fertilizers are used on cultures for the production of castor beans (Cavalcanti et al, (2015).…”
Section: Amounts Of Camentioning
confidence: 99%
See 2 more Smart Citations